Research of strained-and-stressed state of supporting structure of track machine KRS-1 - Tovt, B. M.; Dzichkovskyy, E. M.; Kryvchykov, O. E. (Science and Transport Progress, 2012)
In this article the results of analytical and experimental research of the strained-and-stressed state of supporting structure of the track machine KRS-1 are presented. The analytical research is executed with the use of finiteelement method (FEM). The results of analytical research are used during realization of running dynamic durability tests. The results of experimental and analytical research are compared. On the basis of analysis of the obtained calculation and experimental data the estimation of durability of supporting structure of the track machine KRS-1 is performed.